A study on the effects of groundnut shell ash on strength characteristics of soil - O. Ajala, M.; J. Akinyede, K.; O. Adunoye, G.; J. Akintola, I. (International Journal of Advanced Geosciences, 2020)
This study investigated the effect of groundnut shell ash (GSA) on the strength of selected lateritic soils, with a view to determining the optimum percentage of GSA that will give the best strength properties of the soils. Soil samples were collected from two different borrow pits and identified as sample A and sample B respectively. Preliminary tests (Natural moisture content, specific gravity, grain size analysis, Atterberg limit) and engineering tests (compaction and unsoaked California bearing ratio (CBR)) were conducted on the soil samples in their natural state. GSA was then added to the soils at 2 %, 4 % and 6 % proportions. Atterberg limits, compaction and unsoaked CBR tests were conducted for each addition of GSA. The results showed that there was much improvement in the properties of the soils, with values of plasticity index (PI) reducing from 23.02 % (at 0 % GSA) to 12.55 % (at 6 % GSA) for sample A; and 35.14 % (at 0 % GSA) to 2..54 % (at 6 % GSA) for sample B. It was also observed that addition of GSA generally caused reduction in optimum moisture content (OMC) with an increase in corresponding maximum dry density (MDD). For sample A the maximum value of unsoaked CBR (17 %) was obtained at 2 % GSA, while for sample B, maximum CBR value (4 %) was obtained at 4 % GSA. It was concluded that GSA could be used to significantly improve the strength of lateritic soil.Â Â